Tram squealing noise and its impact on human health - Eva Panulinova; Slávka Harabinová; Lubica Argalášová (Noise and Health, 2016)
Introduction: Tramway has become a serious urban noise source in densely populated areas. The disturbance from squealing noise is significant. Curve squeal is the very loud, tonal noise emitted by tram operation in tight radius curves. Studies had reported a relationship between noise levels and health effects, such as annoyance, sleep disturbance, and elevated systolic and diastolic blood pressure. Materials and Methods: This study aimed to analyze the wheel squeal noise along the tramway line in Košice, Slovakia, review the effects on human health, and discuss its inclusion in the design method. To observe the influence of a track curve on noise emission, several measurement points were selected, and the noise emission was measured both in the curve and in the straight lines employing the same type of permanent way. Results: The results in the sections with the radius below 50 m were greatly affected by the presence of a squeal noise, while the resulting noise level in the sections with the radius above 50 m depended on their radius. The difference between the average values of LAeq with and without the squeal in the measurement points with the radius below 50 m was 9 dB. The difference between the measurements in the curve sections with the radius below 50 m and those in the straight line was 2.7 dB. Conclusion: The resulting noise level in general was influenced by the car velocity and the technical shape of the permanent way. These results can be used in noise prognoses and in the health effect predictions.